(untitled) (Journal Of Educational and Psychological Researches, 2016)
It has become the subject of the environment and its problems during the last three decades of the important topics and dangerous that gained the attention of researchers in this regard as especially with the worsening repercussions severe, and turned out to be hot issues impose themselves urgently everywhere in the world, not concerned with the environment and specialists out, but also on all people wherever they are, regardless of their standard of living, and the circumstances of their lives, and their level of education and culture because the relationship of man with environment relationship since antiquity as relied upon to provide what they need him to stay, and through the stages of the development of civilization has made some attempts to keep it, but faced difficulty because it is controlled by the and the investor have all become influenced by them and even affected, as indicated many of the studies and research studies and research that dealt with the environmental theme and its problems and the need for the development of environmental awareness, some of which stressed the need for the curriculum include environmental issues and problems and seeking to develop environmental awareness . Including, Dspoto Despot study (1977) and the study of Nelson NeLSON ((1993 Shafei and study (1990) and the study of Abdul Salam (1991). Clear from this task rests curriculum planners selected elements of the environment are closest to the lives of learners and the most suitable levels of maturity tasks and curriculum designers to expand the environmental department and deepen the level of intake of the problems in front of children to increase their awareness and discover their preparations and grow their abilities and increase the depth of experience that this process is done gradually systematic and foundations sound science. In order not to waste our efforts in posters and celebrations for the environment, or at festivals and letters of the theory, we must proceed from the real bases and studying the issue through our own potential, without underestimating or exaggerating through scientific objective view that rely on inventory pros and cons, and allow the integration of environmental Thread in the national plan and all of its activities, especially the education, so taken advantage of the possibilities more fully in the development of the pillars of strength and address the environmental drawbacks since they occur. Herein lies the problem of the research to identify the philosophy of geography curricula in the diagnosis and treatment of environmental problems .